2008
DOI: 10.1249/mss.0b013e31817e32a3
|View full text |Cite
|
Sign up to set email alerts
|

Leg Power Asymmetry and Postural Control in Women with Multiple Sclerosis

Abstract: These data provide new evidence of a potential role for KE strength asymmetries in the symptomatic fatigue and physical dysfunction of persons with MS, possibly through an effect on postural stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
134
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(151 citation statements)
references
References 39 publications
12
134
1
4
Order By: Relevance
“…Participants stood quietly on the force plate for 20 seconds with eyes open and directed forward gaze. Overall, the women with MS had greater Center-of-Pressure (COP) sway in the antero-posterior direction (mean=7.52 mm) than the age-matched controls (mean=4.33 mm) [21]. Another study of 16 persons with MS and 16 sex-matched controls used a similar static posturography protocol (i.e., participants stood quietly on a force plate with eyes open and directed forward for 30 seconds) [22].…”
Section: Evidence For Physiological Deconditioning In Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants stood quietly on the force plate for 20 seconds with eyes open and directed forward gaze. Overall, the women with MS had greater Center-of-Pressure (COP) sway in the antero-posterior direction (mean=7.52 mm) than the age-matched controls (mean=4.33 mm) [21]. Another study of 16 persons with MS and 16 sex-matched controls used a similar static posturography protocol (i.e., participants stood quietly on a force plate with eyes open and directed forward for 30 seconds) [22].…”
Section: Evidence For Physiological Deconditioning In Msmentioning
confidence: 99%
“…Another study reported that persons with mild MS-related disability who had a higher O 2 cost of walking took slower (r=-0.25) and shorter (r=-0.32) steps, while spending a greater percentage of time in double support (r=0.27), based on measurements from a GaitRite electronic walkway during comfortable walking pace [39]. Other studies have reported that lesser peak isometric torque and greater torque asymmetries were associated with worse timed 25-foot walking (T25FW) performance in MS [20,21]. One study examined the association of peak torque in knee flexors and extensors with 2-minute walk test (2MWT) distance in 52 persons with mild and moderate MS disability.…”
Section: Walking Outcomesmentioning
confidence: 99%
“…Measurements of height, weight, leg spasticity (using the MASS), comfortable walking speed, and muscle strength preceded 15 min of treadmill walking. The more-and lessaffected sides of patients with MS and strong/weak sides of nondisabled controls were determined from cumulative leg strength since it is known that leg muscle groups are most commonly affected in patients with MS [6,[24][25][26]. The maximal voluntary contraction forces for knee extension and flexion of both legs were summed for each participant, and the leg with the highest additive forces was classified as the stronger/less-affected leg.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Lower-limb muscle weakness [2], with greater weakness on one side of the body [3][4], is a common symptom and may contribute to the walking difficulties frequently experienced by patients with MS [5]. Moreover, patients with MS have been shown to exhibit decreased postural and trunk control [6][7], although very little is known about core muscle activity during walking in this population.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we used dynamic posturography to objectively quantify balance in PwMS because this is the gold standard objective measure of standing postural control and because this has been used previously to quantify balance in PwMS [3][4][11][12]. Recent posturography studies have demonstrated specific performance abnormalities on posturography in PwMS, including delayed automatic postural responses to backward translations [13] and abnormal postural sway when sensory inputs are removed [5].…”
Section: Introductionmentioning
confidence: 99%